Formação jurídica do Brasil: uma história do federalismo à brasileira - Daniel Cabaleiro Saldanha (2017)
The present thesis investigates the historical outline of the development of the Brazilian juridical and political formation, going through the distinct phases of development of its positive law, as well as passing through mentalities and political thoughts, which have been defining the destinies of our national formation. In addition to that, this thesis aims to comprehend the various factors that influenced the shaping of our federative institutional architecture, so as to demonstrate that the Brazilian contemporary federative project complies with oligarchic interests, to the detriment of genuine democratic values, due to its excessive territorial fragmentation of political power.